Market reactions to non‐market strategy: Congressional testimony as an indicator of firm political influence. (10th May 2019) - Ridge, Jason W.; Ingram, Amy; Abdurakhmonov, Mirzokhidjon; Hasija, Dinesh
Abstract: Research Summary : We argue that because influence in the political arena can net benefits for firms, investors will respond favorably to indications of firm political influence. We focus on testimony before Congress because it is one of the most highly sought after and influential points of governmental access. Our findings indicate that firms reap positive abnormal returns surrounding Congressional testimony and that investors respond more favorably to aspects of testimony that indicate additional political influence (i.e., witness status, testimony length, and committee jurisdiction). Further, we find regulatory risk strengthens the effect of witness status and testimony length while Congressional negativity strengthens the effect of witness status. Taken together, our results suggest that investors respond favorably to indications that firms have influence in the political arena. Managerial Summary : Our findings showcase that investors react positively to firm Congressional testimonies and their attributes, such as the status of a firm representative, the length of the testimony, and the committee industry jurisdiction. Further, we also find that investors will respond even more positively to these Congressional testimony attributes when a firm is facing high regulatory risk and when the Congressional representative's tone is negative. In general, our findings suggest that firms may gain market returns through obtaining public access to Congressional committees.